Evaluating umbilical masses: lessons learned from three elderly patients - Soo, Tze Hui; Ganapragasam, Marylyn; Suppiah, Subapriya; Bahari, Norafida (Springer Science and Business Media, 2024)
The umbilicus, an essential embryonic organ, connects the foetus to the placenta. Postnatally, its remnants can lead to both benign and malignant lesions. Tumour metastasis to the umbilicus, though rare, poses significant diagnostic and therapeutic challenges due to overlapping clinical and radiological features with benign conditions. In this case series, we present three cases of elderly women with similar presentations of umbilical or infraumbilical lesions, investigated using standard imaging protocols, which subsequently led to different diagnoses and management plans. Case 1 involves a 64-year-old postmenopausal woman, who presented with an enlarging umbilical mass and serous discharge. Imaging revealed a vascularized lesion in the umbilicus and a suspicious adnexal mass, which was confirmed to be a Sister Mary Joseph nodule secondary to high-grade serous carcinoma of the right ovary. Case 2 involves an 80-year-old diabetic woman, who presented with a painful umbilical mass. Imaging revealed an aggressive-looking umbilical lesion, which was confirmed to be liposarcoma. Case 3 involves an 80-year-old woman, who presented with infraumbilical abdominal swelling and fever. Imaging revealed an infected urachal cyst. Histopathology confirmed an abscess associated with Actinomycetes infection. An umbilical lesion in an adult, particularly an elderly patient, that does not respond to typical treatment should raise the suspicion of a more sinister diagnosis. Integration of clinical, radiological, and pathological data is crucial for accurate diagnosis and effective management.